(untitled) (DAPesquisa, 2021)
Traditional material selection starts from a concept or product to research and definition of suitable materials for the project. However, in cases of use of new materials or unconventional materials an inversion occurs: starting with a material for research and definition of possible products. The purpose of reversing the selection of materials is to introduce a new material or an unconventional material on the market. This paper presents an inverted material selection model proposal, consisting of the material characterization steps, consideration of environmental aspects, comparison with conventional materials, manufacturing processes and definition of applications. Based on this model, two case studies were carried out with sustainable materials: composites with rice husks and porongo. With the case studies, it was possible to validate the inverted material selection model.